China's old churches : the history, architecture, and legacy of Catholic sacred structures in Beijing, Tianjin, and Hebei Province - Sweeten, Alan Richard (Studies in the history of Christianity in East Asia, 2020)
"China's Old Churches, by Alan Sweeten, examines the history of Catholicism (1600 to the present) as reflected by the location, style, and details of sacred structures in three crucial north China areas. Examined are the most famous and important churches in the urban settings of Beijing and Tianjin as well as lesser-known ones in rural Hebei Province. Missionaries built Western-looking churches to make a broad religious statement important to themselves and Chinese worshippers. Non-Catholics, however, tended to see churches as socio-politically foreign and invasive. The physical-visual impact of church structures is significant. Today, restored old and new churches are still mostly of Western style, serving a growing number of Catholics who actively support a Marian movement"--